Dietary strategies and nutritional supplements in the management of heart failure: a systematic review - Yu, Xinyi; Chen, Qilan; Xu Lou, Inmaculada (Frontiers in Nutrition, 2024)
Background and objective: Heart failure (HF) is a syndrome of increased intracardiac pressure or decreased cardiac output. There is a lack of conclusive evidence to recommend the regular use of any dietary supplement in patients with HF. However, certain studies have shown nutritional interventions to be beneficial for patients with HF. Therefore, the purpose of this systematic review was to understand and map the updates of dietary interventions and nutritional supplementation measures related to patients with HF over the past 5 years. Study design: A systematic review. Methods: The PubMed, Web of Science, Scopus, and Cochrane Library databases were searched for randomized clinical trials on the association between dietary interventions and nutritional supplements and HF published between 2018 and 2023. A total of 17554 documents were retrieved, of which 198 were finalized for inclusion. Results: The findings suggest that individualized nutritional support reduces mortality and risk of major cardiovascular events in chronic heart failure inpatients at high nutritional risk. Tthe Mediterranean diet improves functionality, quality of life, and cardiac function. Additionally, supplementation with thiamine, ubiquinol, D-ribose, and L-arginine enhances left ventricular ejection fraction. Probiotic yogurt may effectively improve the inflammatory and antioxidative status of chronic heart failure. Whey protein and melatonin have a positive effect on improving endothelial function in HF patients. Conclusion: Certain dietary interventions and nutritional supplements may provide some benefit to patients with HF. However, there is no relevant definitive evidence on the impact of nutritional interventions on the prognosis of HF, and more high-quality clinical trials are needed for further in-depth studies.